Dietary Fat Patterns and Outcomes in Acute Pancreatitis in Spain - García-Rayado, Guillermo; Varela-Moreiras, Gregorio; Lanas, Ángel; Ferrández, Ángel; Balza-Lareu, Nelly; Cervera, Juan I.; Bodenlle-Bello, María P.; Argüelles-Arias, Ana M.; Latorre, Patricia; Udaondo-Cascante, María A.; Soria-de-la-Cruz, María J.; Lariño-Noia, José; et al. (Frontiers in Medicine, 2020)
Background/Objective: Evidence from basic and clinical studies suggests that unsaturated fatty acids (UFAs) might be relevant mediators of the development of complications in acute pancreatitis (AP). Objective: The aim of this study was to analyze outcomes in patients with AP from regions in Spain with different patterns of dietary fat intake. Materials and Methods: A retrospective analysis was performed with data from 1,655 patients with AP from a Spanish prospective cohort study and regional nutritional data from a Spanish cross-sectional study. Nutritional data considered in the study concern the total lipid consumption, detailing total saturated fatty acids, UFAs and monounsaturated fatty acids (MUFAs) consumption derived from regional data and not from the patient prospective cohort. Two multivariable analysis models were used: 1) a model with the Charlson comorbidity index, sex, alcoholic etiology, and recurrent AP; 2) a model that included these variables plus obesity. Results: In multivariable analysis, patients from regions with high UFA intake had a significantly increased frequency of local complications, persistent organ failure (POF), mortality, and moderate-to-severe disease in the model without obesity and a higher frequency of POF in the model with obesity. Patients from regions with high MUFA intake had significantly more local complications and moderate-to-severe disease; this significance remained for moderate-to-severe disease when obesity was added to the model. Conclusions: Differences in dietary fat patterns could be associated with different outcomes in AP, and dietary fat patterns may be a pre-morbid factor that determines the severity of AP. UFAs, and particulary MUFAs, may influence the pathogenesis of the severity of AP.